1999
DOI: 10.1089/104454999315376
|View full text |Cite
|
Sign up to set email alerts
|

Function and Sequence Analyses of Tumor Suppressor Gene p53 of CHO.K1 Cells

Abstract: The tumor suppressor gene p53 plays an important role in guarding genomic integrity. When induced in response to environmental results, the gene product of p53 functions as a transcription factor to transactivate genes involved in arresting the cell cycle and as a facilitator of DNA repair. In contrast, the status of p53 in Chinese hamster ovary (CHO) cells, commonly used as a model system for various studies including those involving the cell cycle and transformation, remains an enigma. In this study, the fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…The presence of caffeine retards the entry of cells into the G2/M phase after UVc or ␥-ray radiations and perfectly mimics a G2/M override if the cell proliferation kinetics are ignored. 13 Similar experiments performed in our laboratory with the Chinese Hamster Ovary (CHO-K1) cell line which contains a missense mutation for p53 at codon 211 (Thr3 Lys) 14,15 led to identical conclusions (unpublished results).…”
supporting
confidence: 57%
“…The presence of caffeine retards the entry of cells into the G2/M phase after UVc or ␥-ray radiations and perfectly mimics a G2/M override if the cell proliferation kinetics are ignored. 13 Similar experiments performed in our laboratory with the Chinese Hamster Ovary (CHO-K1) cell line which contains a missense mutation for p53 at codon 211 (Thr3 Lys) 14,15 led to identical conclusions (unpublished results).…”
supporting
confidence: 57%
“…Previously, we have shown that p21 (waf1/cip1) mRNA was not detected in UV-irradiated CHO-K1 cells [Tzang et al, 1999a]. The absence of p21 expression was confirmed at the protein level by the Western analysis (Fig.…”
Section: Deregulation Of Cdk2 Activity Is Associated With Uv-induced supporting
confidence: 53%
“…We have previously reported that UVC irradiation (at 25 J/m 2 ) causes significant apoptosis in Chinese hamster ovary cells (CHO-K1) [Tzang et al, 1999b] and expression of the p21 (Waf1/Cip1) gene is absent despite the induction of p53 and gadd45 in the UV-irradiated cells [Tzang et al, 1999a]. p21 (Waf1/Cip1) is an universal inhibitor of cyclin-dependent kinases (Cdks), which is induced during DNA damage [Harper et al, 1993;Xiong et al, 1993;Dulic et al, 1994;Michieli et al, 1994].…”
mentioning
confidence: 99%
“…How valid are CHO cells as a model for studying the FA pathway? The Tp53 defect in CHO cells [Lee et al, 1997;Hu et al, 1999;Tzang et al, 1999] …”
Section: Resultsmentioning
confidence: 99%